HUBUNGAN POLA KONSUMSI ZAT GIZI MAKRO DAN MIKRO DENGAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Listiana, Listiana; Ahmad Rizal, Arie krisnasary (JURNAL MEDIA KESEHATAN, 2017)
Hypertension is a condition that shows a person's blood pressure ≥140 mmHg for systolic and / or ≥90 mmHg pressure for diastolic pressure. The purpose of this research is to know the correlation between consumption pattern of macro and micro nutrients to blood pressure of hypertension patient in RSUD dr.M.Yunus Bengkulu Year 2017. Method: This research is an analytic survey, with cross sectional design. The location of this research is in poly disease in RSUD dr.M.Yunus. Samples were hypertension patients who treated in poly disease in RSUD Dr.M.Yunus Bengkulu as many as 50 samples, taken with chi square technique. Data of macro and micro nutrient intake was obtained through form food frequency questioner (FFQ). The data obtained were analyzed using chi square test. There is no association of protein with hypertension, no association of fat with hypertension, no carbohydrate relationship with hypertension, no sodium relationship with hypertension, no calcium relationship with hypertension, no potassium relationship with hypertension, no magnesium relationship with hypertension, no there is correlation of fiber with hypertension, there is no correlation of vitamin D with hypertension in RSUD dr.M.Yunus Kota Bengkulu year 2017. There is no correlation of consumption pattern of macro and micro nutrients with blood pressure in hypertension patient in poly disease in RSUD Dr.M. Yunus bengkulu in 2017. The need for an active family role related to the motivation and diet of hypertensive patients